Reconstruction of Police Legal Policy in Handling Eigenrichting Due to Low Public Trust in the Criminal Justice System - M. Aditya Perdana; Benyamin Lufpi; Kif Aminanto (Indonesian Journal Publisher, 2026)
Vigilante action (eigenrichting) is a social phenomenon that signals a crisis of public trust in the criminal justice system and the limited legitimacy of law enforcement institutions in delivering justice in society. The study aims to analyze the factors causing eigenrichting, the weaknesses of legal policies and police strategies in preventing it, and formulate a reconstruction of police legal policies based on strengthening public trust and a preventive approach. The study employs a normative juridical research method under legislative and conceptual approaches through various regulations, legal theories, and doctrines relevant to the criminal justice system and police functions. The results reveal that the rise of vigilantism is influenced by low public trust in law enforcement officers, slow law enforcement processes, weak transparency in case handling, low public legal literacy, and social media, which triggers social vigilantism and instant punishment. In addition, legal policies and police strategies in dealing with eigenrichting are still repressive and have not been optimal in developing a preventive-participatory approach through community policing, digital policing, restorative justice, and an early detection system for social conflict. Therefore, a reconstruction of police legal policy is needed by strengthening transparency in law enforcement, optimizing community policing, developing cyber patrols, enhancing public legal education, and establishing a technology-based social conflict prevention system to realize a humanistic, responsive, and human rights-oriented law enforcement system within a democratic state based on the rule of law.